Metamorphosis: Some Aspects of this Motif in Ovid's Metamorphoses - Neuru, Lucinda L. (My University, 1980)
This thesis is about Ovid's descriptions of the change of the human form into another form, e.g., an animal, stone, body of water or a tree, in his poem, Metamorphoses. The title indicates the importance of this phenomenon, metamorphosis, in that work.
There are about 250 examples of metamorphosis in the poem. Of these, Ovid describes approximately twenty per cent. To describe more might have been boring; to describe less might have left an open question for his audience: how does a metamorphosis work?
Previous work on this subject has been confined to either an attempt at analysis of all examples, or of so few, that Ovid's method of description for these important examples has never been explored.
It has been found that Ovid's purpose was to explain the phenomenon in credible terms, which is his basic method of description generally. His use of previous sources shows that he explained the animal metamorphoses more in terms of prior tradition than the other groups. He seems to have provided a real impetus for change in the portrayal of persons metamorphosing into trees which appear particularly in the post Ovidian sources in art. Ovid appears to have been the most inventive in those descriptions of persons changing into stone.
Keywords: Ovid; metamorphosis; human; animal; water; stone; tree